2021
DOI: 10.1159/000515658
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Blood Pressure Recovery Measured Using a Sphygmomanometer Is Not Associated with Physical Performance or Number of Falls in Geriatric Outpatients

Abstract: <b><i>Background:</i></b> Orthostatic hypotension (OH) and impaired OH recovery derived from beat-to-beat blood pressure (BP) measurements are associated with detrimental clinical outcome, but the clinical relevance of OH recovery assessed using the widely available sphygmomanometer is still unclear. <b><i>Method:</i></b> 635 geriatric outpatients underwent comprehensive geriatric assessment, including orthostatic BP measurements using a sphygmomanometer, during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We included one systematic review and meta-analysis [ 37 ] and 16 original studies [ 38 53 ] on (orthostatic) blood pressure measurements in fallers. In the systematic review and meta-analysis by Mol et al [ 37 ], the relevance of blood pressure measurement methodology in OH-related falls was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included one systematic review and meta-analysis [ 37 ] and 16 original studies [ 38 53 ] on (orthostatic) blood pressure measurements in fallers. In the systematic review and meta-analysis by Mol et al [ 37 ], the relevance of blood pressure measurement methodology in OH-related falls was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent (sphygmomanometer) blood pressure measurements during AS were used in four (4/16) studies [ 48 , 50 , 52 , 53 ]. In one study [ 50 ], prevalence of OH was higher at the 30s measurement compared to the 3 min measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 13 studies that utilized sphygmomanometers, but did not specify which type, 6 reported a positive association: QA 6.8 (range 5–9) ( 36 , 145 , 147 , 150 , 151 , 153 ). Seven reported no association: QA 7.5 (range 4–9) ( 43 , 60 , 122 , 146 , 148 , 149 , 152 ).…”
Section: Resultsmentioning
confidence: 99%